Structural Model of Identity Instability Based on Object Relations and Childhood Trauma with the Mediating Role of Difficulties in Emotion Regulation in Adolescents with Self-Harming Behaviors - Malekzadeh, Fatemeh Zhinous; Mohammadipour, Mohammad; Jajarmi, Mahmoud (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: This study aimed to determine the fit of a structural model of identity instability based on object relations and childhood trauma, with the mediating role of difficulties in emotion regulation in adolescents with self-harming behaviors. Methods and Materials: The research method was descriptive and correlational. The statistical population in this study consisted of all male and female high school students with self-harming behaviors from public schools in Gonbad-e Kavus during the 2024-25 academic year. A non-random, purposive sampling method was used, and 310 students were selected as the sample size. Data were collected using the Identity Instability Scale (Lechner, 2023), the Object Relations Inventory (Bell et al., 1986), the Childhood Trauma Questionnaire (Bernstein et al., 2003), and the Difficulties in Emotion Regulation Scale (Bjureberg et al., 2016). Data were analyzed using SPSS version 26 and AMOS version 18, with Pearson’s correlation test and structural equation modeling using partial least squares. The mediating role was tested using the bootstrap method. Findings: The results showed that the experimental model had an acceptable and good fit, and the overall model was confirmed (p< 0.05). Object relations had a direct effect on identity instability in adolescents with self-harming behaviors at 0.152 (p<0.05). Childhood trauma had a direct effect on psychological pain in adolescents with self-harming behaviors at 0.263 (p<0.05). Object relations had a direct effect on difficulties in emotion regulation in adolescents with self-harming behaviors at 0.543 (p<0.05). Childhood trauma had a direct effect on difficulties in emotion regulation in adolescents with self-harming behaviors at 0.210 (p < 0.05). Object relations influenced identity instability with the mediating role of difficulties in emotion regulation in adolescents with self-harming behaviors in an indirect manner (p < 0.05). Childhood trauma influenced identity instability with the mediating role of difficulties in emotion regulation in adolescents with self-harming behaviors in an indirect manner (p < 0.05). Conclusion: Overall, the findings indicate that identity instability in adolescents with self-harming behaviors is the result of a multilayered interaction between early experiences and the characteristics of object relations.